Beep-and-Sleep: Message and Energy Efficient Set Cover - Götte, Thorsten; Kolb, Christina; Scheideler, Christian; Werthmann, Julian (Theor. Comput. Sci.)

Near-Term Effects of Short-Term Study Abroad: A Longitudinal Examination of Learner Perceptions - Müller, Mareike (Frontiers: The Interdisciplinary Journal of Study Abroad)
A relatively small body of research has been conducted on the near- and long-term effects of study abroad (SA) to date. This existing research suggests that SA effects on language skills tend to be volatile, while the impact on various aspects of learners’ personal, academic, and professional development may be longer-lasting. Yet, learner perspectives on the dynamics and durability of such effects, in particular in the context of short-term SA programs, remain largely unexplored. This study hence investigates the near-term impact of short-term SA programs as experienced by students within the first months and years following their sojourns. A qualitative case-study design is employed to examine the accounts of four American students of German, who studied abroad in Austria for four weeks and were interviewed repeatedly over a period of up to 40 months after their sojourns. The results suggest that, from the students’ perspective, many effects deteriorate in the near term, although the overall sojourn experience still appears influential. Abstract in German Nur wenige Forschungsvorhaben haben sich bislang den mittel- bis langfristigen Auswirkungen studentischer Auslandsaufenthalte gewidmet; die bisherige Datenlage deutet jedoch darauf hin, dass die Auswirkungen auf sprachliche Kompetenzen eher unbeständig sind, wohingegen die persönliche, studiums- und berufsbezogene Entwicklung der Lernenden länger von einem Auslandsaufenthalt beeinflusst wird. Die Dynamik und Beständigkeit derartiger Auswirkungen wurden jedoch kaum mit Blick auf kurze Auslandsaufenthalte (≤ acht Wochen) sowie aus der Perspektive der Studierenden erforscht, was die vorliegende Studie insbesondere hinsichtlich mittelfristiger Effekte fokussiert. Mittels eines qualitativen Fallstudiendesigns werden die Interviewdaten vier amerikanischer Deutschlernender untersucht, die sich vier Wochen in Österreich aufhielten und in einem Zeitraum von bis zu 40 Monaten nach ihrem Aufenthalt wiederholt befragt wurden. Die Ergebnisse zeigen, dass viele Auswirkungen eines solchen Aufenthalts aus studentischer Perspektive mittelfristig verblassen, auch wenn der Auslandsaufenthalt im Gesamten weiterhin als einflussreiche Erfahrung wahrgenommen wird.

Musiklandschaften zwischen Rhein und Weser. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Unter Mitarbeit v. Markus Lauert

Distribution Network Optimization: Predicting computation times to design scenario analysis for network operators - Burmeister, Sascha Christian; Schryen, Guido (Energy Systems)

Musiklandschaften zwischen Rhein und Weser – Einführung - Meine, Sabine; Otto, Arnold; Süßmann, Johannes (Musiklandschaften zwischen Rhein und Weser. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Unter Mitarbeit v. Markus Lauert)

Minimum Edge Cuts in Overlay Networks - Schweichhart, Jonas

"Lesungen vor Kindern sind für mich Theater" / Salah Naouras Sicht auf Wirkliches und Mögliches in Autor*innenlesungen für Kinder in der Schule - Kruse, Iris; Maubach, Bernd; Tönsing, Johanna (Salah Naoura)

Held*innenträume. Superheldinnen und Superhelden selbst erdacht / Paderborner Grundschulkinder werden auf die Begegnung mit Salah Naoura vorbereitet - Kruse, Iris; Schäfer, Luisa Maria (Salah Naoura)

Salah Naoura

Biopolitik(en) in Literatur, Film und Serie: Aushandlungs- und Reflexionsräume vom 18. Jahrhundert bis heute

Routing Schemes for Hybrid Communication Networks - Werthmann, Julian; Scheideler, Christian; Coy, Sam; Czumaj, Artur; Schneider, Philipp

Brief Announcement: Distributed Construction of Near-Optimal Compact Routing Schemes for Planar Graphs - Dou, Jinfeng; Götte, Thorsten; Hillebrandt, Henning; Scheideler, Christian; Werthmann, Julian (Proc. of the 42nd ACM Symposium on Principles of Distributed Computing (PODC '23))

Time-Optimal Construction of Overlays - Götte, Thorsten; Hinnenthal, Kristian; Scheideler, Christian; Werthmann, Julian (Distributed Computing)

Aus Erklärvideos lernen - Kulgemeyer, Christoph; Sterzing, Fabian; Hörnlein, Madeleine (Digital Physik unterrichten. Grundlagen, Impulse, Perspektiven)

The Black Humanist Tradition in Anti-Racist Literature: A Fragile Hope - Hartmann, Alexandra

Umsetzung einer optimierten Oberflächenschlitzung zur Wirbelstromverlustreduktion auf der Oberfläche eines additiv gefertigten Permanentmagnet-Rotors - Haase, Michael; Bieber, Maximilian; Tasche, Frederik; Schaper, Mirko; Hoyer, Kay-Peter; Ponik, Bernd; Magyar, Balázs (Proceedings of the 19th Rapid.Tech 3D Conference Erfurt, Germany, 9–11 May 2023)

Bomb the System! Politische Pieces als Partizipationspraktik im öffentlichen Raum - Niemann, Sven (Kunst und Politik. Jahrbuch der Guernica-Gesellschaft. Schwerpunkt: Politisches Graffiti.)

IngridKG: A FAIR Knowledge Graph of Graffiti - Sherif, Mohamed Ahmed; da Silva, Ana Alexandra Morim; Pestryakova, Svetlana; Ahmed, Abdullah Fathi; Niemann, Sven; Ngomo, Axel-Cyrille Ngonga (Scientific Data)
Abstract Graffiti is an urban phenomenon that is increasingly attracting the interest of the sciences. To the best of our knowledge, no suitable data corpora are available for systematic research until now. The Information System Graffiti in Germany project ( Ingrid ) closes this gap by dealing with graffiti image collections that have been made available to the project for public use. Within Ingrid , the graffiti images are collected, digitized and annotated. With this work, we aim to support the rapid access to a comprehensive data source on Ingrid targeted especially by researchers. In particular, we present Ingrid KG, an RDF knowledge graph of annotated graffiti, abides by the Linked Data and FAIR principles. We weekly update Ingrid KG by augmenting the new annotated graffiti to our knowledge graph. Our generation pipeline applies RDF data conversion, link discovery and data fusion approaches to the original data. The current version of Ingrid KG contains 460,640,154 triples and is linked to 3 other knowledge graphs by over 200,000 links. In our use case studies, we demonstrate the usefulness of our knowledge graph for different applications.
Keywords: Library and Information Sciences; Statistics; Probability and Uncertainty; Computer Science Applications; Education; Information Systems; Statistics and Probability

INGRID—Archiving Graffiti in Germany - Niemann, Sven (Document | Archive | Disseminate Graffiti-Scapes)

Local Protocols for Contracting and Expanding Robot Formation Problems - Castenow, Jannik